In Vitro Activities of Voriconazole in Combination with Three Other Antifungal Agents against Candida glabrata - Barchiesi, Francesco (American Society for Microbiology, 2004)
Candida glabrata has recently emerged as a significant pathogen involved in both superficial and deep-seated infections. In the present study, a checkerboard broth microdilution method was performed to investigate the in vitro activities of voriconazole (VOR) in combination with terbinafine (TRB), amphotericin B (AMB), and flucytosine (5FC) against 20 clinical isolates of C. glabrata. Synergy, defined as a fractional inhibitory concentration (FIC) index of ≤0.50, was observed in 75% of VOR-TRB, 10% of VOR-AMB, and 5% of VOR-5FC interactions. None of these combinations yielded antagonistic interactions (FIC index > 4). When synergy was not achieved, there was still a decrease in the MIC of one or both drugs used in the combination. In particular, the MICs were reduced to ≤1.0 μg/ml as a result of the combination for all isolates for which the AMB MIC at the baseline was ≥2.0 μg/ml. By a disk diffusion assay, the halo diameters produced by antifungal agents in combination were greater that those produced by each drug alone. Finally, killing curves showed that VOR-AMB exhibited synergistic interactions, while VOR-5FC sustained fungicidal activities against C. glabrata. These studies demonstrate that the in vitro activity of VOR against this important yeast pathogen can be enhanced upon combination with other drugs that have different modes of action or that target a different step in the ergosterol pathway. Further studies are warranted to elucidate the potential beneficial effects of such combination regimens in vivo.